Efektivitas Komunikasi Interpersonal Pustakawan di UPT Perpustakaan Universitas Andalas - Nabila, Jeihan; Avina, Danira Galuh (Media Pustakawan, 2024)
This study aims to describe the interpersonal communication skills of librarians in the self- circulation services at the Andalas University Library. The background of this research is the ineffective interpersonal communication by librarians, which causes difficulties for users in finding the information they need. This research uses a descriptive qualitative method with data collection techniques such as interviews, observations, and documentation. The study informants consisted of three librarians and two users selected through purposive sampling. Data analysis was carried out through data reduction, data presentation, and verification stages. The results showed that the aspects of openness and empathy among librarians were not effectively applied, while the aspects of supportiveness, positiveness, and equality were well implemented. The lack of openness led to difficulties for users in obtaining the necessary information, while the lack of empathy made users feel neglected. On the other hand, good supportiveness, positiveness, and equality increased the comfort and trust of users. This study suggests the need for training for librarians to improve openness and empathy, as well as regular evaluations of librarians' interpersonal communication skills to ensure optimal service quality. This research is essential for enhancing library service quality and user satisfaction especially in self-circulation service.